2015
DOI: 10.11648/j.earth.s.2015040501.20
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Changes of Caucasus Forest Landscapes

Abstract: Abstract:Caucasus eco-region occupies more than 583 thousand sq km and are represented 25 types, 62 sub-types and 205 genera of landscapes. Due to several climatically contrasting regions the landscapes are quite diverse here. Sub-tropical humid conditions, also experiencing mostly hot, dry weather year-round dominate in the lowland and foothills of Caucasus. forests are mostly concentrated in low-and middle-mountain landscapes. Comparatively little are of forests are concentrated in the lowlands and plains. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The Caucasus ecoregion (Figure 1) is one of the biologically richest yet most highly anthropogenically threatened area (Mittermeier et al, 2011; Nikolaishvili & Dvalashvili, 2015; Shatberashvili et al, 2016) and is at high risk of climate change, especially in its eastern part (IPCC, 2022; Nikolaishvili & Dvalashvili, 2015; Shatberashvili et al, 2016). An alarming forest cover loss in the South Caucasus region (i.e., Georgia, Azerbaijan and Armenia) is predicted in this century due to the climatic crisis (Dagtekin et al, 2020; Dering et al, 2021; Zazanashvili et al, 2011), a pattern already observed in Azerbaijan (Buchner et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Caucasus ecoregion (Figure 1) is one of the biologically richest yet most highly anthropogenically threatened area (Mittermeier et al, 2011; Nikolaishvili & Dvalashvili, 2015; Shatberashvili et al, 2016) and is at high risk of climate change, especially in its eastern part (IPCC, 2022; Nikolaishvili & Dvalashvili, 2015; Shatberashvili et al, 2016). An alarming forest cover loss in the South Caucasus region (i.e., Georgia, Azerbaijan and Armenia) is predicted in this century due to the climatic crisis (Dagtekin et al, 2020; Dering et al, 2021; Zazanashvili et al, 2011), a pattern already observed in Azerbaijan (Buchner et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The present study shows that, in Europe, these areas are located primarily at the northern fringe of the continent (Figure 4), including the coasts of the Barents Sea, which are threatened by human activities and suffer from environmental pollution [81]. Another geodiversity hotspot can be identified in the Caucasus, which also undergoes significant anthropogenic pressure [82,83]. High values for the components of geodiversity were also noted for the highest mountain ranges of western and southern Europe (Figure 4 and Supplementary Materials S1), such as the Alps and the Pyrenees, which experience much higher human population densities than the northern coasts and can also be defined as possible geodiversity hotspots.…”
Section: Geodiversity Evaluationmentioning
confidence: 63%
“…The heterogeneous topography of the region may also continue to act in part as potential future refugia for taxa – as it has in the past (Bilgin, 2011; Homami Totmaj et al., 2021; Médail & Diadema, 2009). However, the diverse terrestrial ecosystems of this unique region are under continuous pressure from anthropogenic interferences, including severe ecosystem fragmentation due to land use and land cover change (Nikolaishvili & Dvalashvili, 2015; Sefidi et al., 2022; Sekercioglu et al., 2011). Therefore, simulation experiments designed to forecast the potential distribution of woody species, including the direction of any potential migration, or an “escape route” under different climate change scenarios are timely and pertinent.…”
Section: Introductionmentioning
confidence: 99%